How band tail recombination influences the open‐circuit voltage of solar cells. (4th July 2021) - Wolter, Max Hilaire; Carron, Romain; Avancini, Enrico; Bissig, Benjamin; Weiss, Thomas Paul; Nishiwaki, Shiro; Feurer, Thomas; Buecheler, Stephan; Jackson, Philip; Witte, Wolfram; Siebentritt, Susanne
Abstract: The power conversion efficiency of solar cells strongly depends on the open‐circuit voltage V OC which, in turn, depends on the recombination activity within the device. A possible source of detrimental charge carrier recombination is band tails. An empirical linear relationship between V OC loss and the Urbach energy of the band tails has been shown in the past. Here we discuss how band tails influence the radiative recombination and the nonradiative recombination in the bulk of the absorber. First, we show through photoluminescence that the band tails can be willfully tuned in state‐of‐the‐art thin‐film Cu (In, Ga)Se2 (CIGSe) absorbers and solar cells on a 20% efficiency level and beyond through the incorporation of alkali atoms. In the second part, we compare our CIGSe results to published results from other solar cell technologies. This comparison reveals that CIGS solar cells follow the previously described empirical trend: an increase in the open‐circuit voltage with decreasing band tails. Finally, we model the influence of tail states on the radiative and nonradiative recombination losses: Radiative recombination is increased because carriers thermalize into the tail states and nonradiative recombination of free carriers in the bands is increased because of Shockley–Read–Hall recombination through the tail states. The comparison with experimental data shows that the influence of tail states is even worse than the increase in radiative and SRH recombination predicted by our model. Our results thus suggest that band tails act as one of the main remaining voltage limitations in the majority of state‐of‐the‐art solar cells. Abstract : Alkali atoms reduce the band tails in Cu (In, Ga)Se2 solar cells on a 20% efficiency level and beyond. A reduction of the Urbach energy E U, which describes the band tails, leads to an increase of the open‐circuit voltage V OC in Cu (In, Ga)Se2 as well as in other solar cell technologies. Our theoretical model shows that the increase in the V OC cannot be explained by typical radiative and nonradiative recombination channels but requires an additional nonlocal recombination channel.